The conjugate hull of a type B semigroup. (18th August 2019) - Li, Chunhua; Pei, Zhi; Xu, Baogen; Huang, Huawei; Xie, Min
Abstract: The purpose of this paper is to study the conjugate hull of a type B semigroup. After obtaining some properties and constructions of right translations of the semilattice of a type B semigroup, we give some structure theorems of such semigroups. Finally, we prove that the conjugate hull of an arbitrary type B semigroup is closed under its operation.